Mild Mechanic Stimulate on Acupoints Regulation of CGRP-Positive Cells and Microglia Morphology in Spinal Cord of Sciatic Nerve Injured Rats - Yi-zhen, Li; Run-pei, Miao; Tian-yuan, Yu; Wan-zhu, Bai; Jing-jing, Cui; Meng-qian, Lu; Yi, Shen; Yu-ting, Luo; Shuai, Shao; Yu-mo, Zhang; Yan-jun, Mo; Tao-tao, Lv; et al. (Frontiers in Integrative Neuroscience, 2019)
Objective To observe the effects of mild mechanic stimulate on acu-points on spinal motor neurons and active substances of sciatic nerve injury in rats and to explore a morphological basis for the recovery of motor function in rats with sciatic nerve injury by using mild acupuncture. Acupuncture in the local area of the injury may cause further damage to the peripheral nerve injury. We believe that mild mechanical stimulation on the surface by using some specific acu-points can also have a positive effect on nerve repair. This method called Chinese tuina has existed for more than 2,000 years in China. Methods This study established a rat model by using sciatic nerve crush injury. Rats received Chinese tuina in accordance with the principle of three methods and three points, once daily for 20 days. The labeled neuronal cell body was used to evaluate the fiber recovery after rats’ sciatic nerve injuring by using neural tracing technique. Our team studied motor neuronal cell bodies, CGRP-positive cells and microglia of damaged sciatic nerves which were stained with fluorescent triple staining by adopting confocal multi-layer scanning technique, and then analyzed changes in neuronal activity distribution and expression with the changes of time and treatment by the method of morphological description. Results The injury of sciatic nerve decreased the survival of motor neurons, affected CGRP-positive cells and activated microglia in ventral horn of spinal cord. Compared with the model group, the survival of spinal ventral horn motor neurons was increased through tuina intervention. The swelling of CGRP-positive cells was alleviated and the degree of microglia activation was less than that of the model group. Conclusion This study used visual morphological findings to assess changes in neurons and active substances with time after injuring of peripheral nerve, and demonstrated that peripheral mild acupuncture intervention improved the capacity of neurofibrillary axoplasmic transport, regulated microglia activation, and significantly promoted the recovery of sciatic nerve injury.